PEMETAAN DAN EVALUASI TEKNIS JARINGAN DISTRIBUSI AIR BERSIH DI DESA KEMUNING LOR - Pradita Dewi Hidayah; Indarto Indarto; Elida Novita (Faculty of Agricultural Technology, University of Jember, 2016)
This research aims to describe water distribution network and to evaluate technical performance of water distribution network. Research was implemented at Kemuning Lor village, sub-district Arjasa, in Jember Regency. This village located at about 12 km from Jember City to the direction of Argopuro mountain areas. Field survey a long the network was effectued using GPS. Secondary data were obtained from interview with stakeholders at the vilalage. The Map was produced by means of QGIS. Technical evaluation of physical network performance was done using EPANET version 2.0 software. The main input for this study are: discharge measurement, GPS data, datum, length of segment, pipe-diameter and roughness coefficient. The output data in the form of pressure and speed of the water at the junction. Furthermore, the result from EPANET are then compared to existing standard parameters. This research produce a map that visualize the water distribution network and the report of network performance in technical aspect. Finally, it is conclude that in general the existing water distribution netowork is still in compliance with the standard. However, at a fews locations on the network need to be adapted to the existing standard of pressure and speed. Keywords: network, water distribution, Epanet, evaluation of performance